The Practices of Disclosure and Management of Medical Errors by Surgical Trainees-Better Preparing A Future Surgeon (Journal of Surgical Sciences, 2019)
Abstract not availableJournal of Surgical Sciences (2014) Vol. 18 (2) : 43-44